2008
DOI: 10.1029/2007ja012649
|View full text |Cite
|
Sign up to set email alerts
|

Properties of magnetosheath mirror modes observed by Cluster and their response to changes in plasma parameters

Abstract: [1] Mirror modes are large amplitude nonpropagating compressive structures frequently observed in the magnetosheath. They appear in the form of quasi-sinusoidal oscillations in the magnetic field, profound magnetic decreases (dips) or magnetic enhancements (peaks), accompanied by a corresponding anticorrelated signature in plasma density. In this study we present an analysis of the properties of mirror mode structures in the magnetosheath of the Earth based on a database of Cluster observations and also a deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
240
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(287 citation statements)
references
References 47 publications
36
240
1
Order By: Relevance
“…The timescale of MMs in the solar wind at 0.72 AU is reported to vary from a few seconds up to 40 s (Zhang et al, 2009). Similar durations are also reported in the magnetosheath of the Earth (Soucek et al, 2008). We therefore expect the MMs to have similar durations in ICME-driven sheath regions.…”
Section: Mirror Mode (Mm) Identificationsupporting
confidence: 54%
See 4 more Smart Citations
“…The timescale of MMs in the solar wind at 0.72 AU is reported to vary from a few seconds up to 40 s (Zhang et al, 2009). Similar durations are also reported in the magnetosheath of the Earth (Soucek et al, 2008). We therefore expect the MMs to have similar durations in ICME-driven sheath regions.…”
Section: Mirror Mode (Mm) Identificationsupporting
confidence: 54%
“…Studies of planetary magnetosheaths have shown that peak-like MMs occur in mirror unstable plasma, whereas dip-like MMs are observed in both mirror stable and unstable plasma (e.g., Soucek et al, 2008;Califano et al, 2008;Génot et al, 2009a). Furthermore, in 2-D hybrid simulations, dip-like MMs were formed in low β plasma, whereas peak-like structures were generated in high β plasma (Shoji et al, 2012).…”
Section: M Ala-lahti Et Al: Mirror Mode Wave Occurrence In Icme-mentioning
confidence: 99%
See 3 more Smart Citations